A role for synapsin 2a oligomerization in maintaining a reserve pool of synaptic vesicles - Zhang, Minchuan (Nanyang Technological University, 2022)
Although it is known that synapsins maintain a reserve pool (RP) of synaptic vesicles (SVs) within presynaptic terminals, the precise mechanism involved in this action remains elusive. I have tested the role of synapsin oligomerization in this process by examining the ability of an oligomerization-deficient mutant of synapsin 2a to rescue the RP defects of cultured glutamatergic neurons from synapsin triple knock-out (TKO) mice. My results showed that the oligomerization-deficient synapsin 2a mutant was not able to rescue the defective RP size, impaired RP mobilization, and enhanced inter-bouton movement of SVs in TKO neurons. This differs from the effects of wild-type synapsin 2a, which can rescue all of these phenotypes. Therefore, the loss of oligomerization prevents synapsin 2a from maintaining the RP of SVs within presynaptic terminals. My results support the idea that oligomerization of synapsin 2a is important for maintaining glutamatergic SVs within the RP of presynaptic terminals, thereby providing a molecular explanation for how the RP can supply SVs during sustained synaptic activity.